Single and joint effect of the basal region of chromosome 2 and centromeric region of chromosome 8 on morphological and fruit quality traits in tomato - Green, Gisela Yael (2016)
The goal of this study was to estimate the single and joint effect of the basal region of chromosome 2 and centromeric region of chromosome 8 on morphological and fruit quality traits in tomato (Solanum lycopersicum). The analysis was performed in a population derived from a cross between Rio Grande of S. lycopersicum and LA1589 of S. pimpinellifolium that segregates for both genomic regions. Four major QTLs were found on chromosome 2 and three on chromosome 8, all of them related with morphological traits. QTLs for fruit shape index, proximal fruit end angle and distal fruit end protrusion showed epistatic interaction. Both genomic regions (fs2.1 and fs8.1) explained 62, 47 and 46 % of the phenotypic variability for fruit shape index, proximal fruit end angle and distal fruit end protrusion respectively. Minor QTLs were detected for other morphological and quality traits such as color, pH and fruit shelf life on chromosomes 2 and 8. Only single genomic region effects were found for quality trait. On the other hand, fs2.1 and fs8.1 regions control several fruit morphology attributes following a digenic linear additive model with epistatic interactions.